Antimicrobial, antioxidant and calcium channel blocking activities of Amberboa divaricata - Iqbal, Shahid Muhammad; Mushtaq, Aamir; Jabeen, Qaiser (Bangladesh Journal of Pharmacology, 2014)
Traditional healers in Pakistan use the herb Amberboa divaricata as tonic, aperiant, deobstruent, febrifuge, antidiarrheal, antiperiodic, antipyretic, anti-cough and in skin disorders. In vitro tissue experiments were carried out on rabbit jejunum to elucidate the possible mechanism of its prescribed effects on gastrointestinal tract, while antibacterial and antioxidant experiments were performed to provide pharmacological evidence of its traditional use in skin disorders. The 70%methanolic crude extract of A. divaricata produced dose dependent relaxation in isolated rabbit jejunum tissue in a concentration range of 0.13.0 mg/mL (n=5). Calcium response curves were constructed at concentration of 0.03 and 0.1 mg/mL (n=5), which produced rightward shift in a pattern similar to that of verapamil, confirming the calcium channel blocking activity. Agar disc diffusion assay at a concentration of 10 mg crude extract/disc showed clear zones of inhibition.